The German severe asthma patient: Baseline characteristics of patients in the German Severe Asthma Registry, and relationship with exacerbations and control. (April 2022) - Korn, Stephanie; Milger, Katrin; Skowasch, Dirk; Timmermann, Hartmut; Taube, Christian; Idzko, Marco; Voß, Hans Werner; Holtdirk, Annette; Hamelmann, Eckard; Buhl, Roland
Abstract: Introduction. The German Asthma Net Severe Asthma Registry is collecting long-term data from a large cohort of patients aged ≥6 years with severe asthma. This manuscript presents their baseline characteristics, and identifies relationships with exacerbations and/or poor asthma control. Methods. The registry is collecting routine clinical parameters including: demographics and medical history; disease characteristics (Asthma Control Questionnaire [ACQ]-5, forced expiratory volume in 1 s [FEV1 ]); exacerbations; and biomarkers (eosinophils, immunoglobulin E [IgE], fractional exhaled nitric oxide [FeNO]). Results. These analyses include data from 2011 patients at 72 sites (91.9% adult). Children (6–17 years) were more likely to be male, whereas more adults were female (males: children/adults 62%/41%). Most were receiving inhaled corticosteroid/long-acting β2 -agonist combinations (78%/81%); 38.0% of adults were receiving systemic steroids. Asthma control was suboptimal in both groups: 21.5%/13.3% were controlled; 10.4%/49.1% were symptomatic; 33.1%/37.2% received emergency asthma treatment in the previous year. Median blood eosinophil (400/238 cells/μL) and IgE levels (494/186 IU/mL) were higher in children; FeNO was lower (19/35 ppb). Patients with ≥2 exacerbations in the previous year had lower FEV1 (absolute and % predicted) and IgE, and higher ACQ-5, FeNO and blood eosinophil levels (all p < 0.05). There was a weak, negative correlation between ACQ-5 and FEV1 % predicted in adults (p < 0.001). Conclusions. These analyses characterise the typical German patient with severe asthma, and provide information on their overall care. Their planned long-term follow-up will assess whether asthma control can be optimised, how best to do so, and most importantly how such optimisation can benefit patients. Highlights: The German Asthma Net Severe Asthma Registry is collecting long-term data from over 2000 patients. This manuscript reports baseline characteristics of the recruited cohort. Asthma control was suboptimal: more than 30% required emergency asthma treatment. Long-term follow-up will assess whether (and how) asthma control can be optimised.